Self-disclosure during adolescence: exploring the means, targets, and types of personal exchanges. (February 2020) - Vijayakumar, Nandita; Pfeifer, Jennifer H
Abstract : Sharing information about oneself, or self-disclosing, is a fundamental interpersonal process that facilitates the attainment of key developmental milestones during adolescence. Changes in self-disclosure behaviors may reflect or support the social reorientation that sees children become increasingly reliant on peers for social and emotional support. Neuroimaging research has highlighted protracted maturation of the structure and function of brain regions that support social cognitive and reward processes underlying self-disclosure during adolescence. This review explores behavioral and neural trends in self-disclosure during adolescence, including research that uses novel experimental paradigms to extend the field beyond self-report measures. Findings show that certain aspects of self-disclosure behavior have adapted to changing social environments, but they remain intrinsically valued across the adolescent period and are essential for relationship development, identity formation and overall self-worth and well-being.